Modeling of particle dynamics in a vertical three – layer – mixer of bulk matters - Мироненко, Анатолий Прохорович; Завгородний, Алексей Иванович (Eastern-European Journal of Enterprise Technologies, 2014)
The mathematical model, describing scattering dynamics of grain mixture particles at the top of the three-layer vertical mixer, equipped with cantilever shafts and impeller is given in the paper. The proposed model allows considering the aerodynamics of complex vortex flows, created by rotating cantilever shafts, and grain particle interaction with the screw. The aerodynamics model is based on the equations for ideal incompressible fluid, which are solved by the discrete vortex method. Grain particle movement is simulated within the particle dynamics model. For that, the equations of particle motion on the rotating helical surface were obtained. A simple criterion for the cantilever impeller operation efficiency in the mixing process, based on the introduced scattering coefficient was proposed. The proposed model allows conducting a computational experiment to determine the optimal impeller design parameters and the optimal mixer operating modes. The calculations confirmed the efficiency of installing cantilever shafts with impeller in the vertical mixer. The results of numerical calculations, performed on this model were used in the design and manufacture of vertical feed mill small-sized installation VFMSSI-04.